Intimal Arteritis and Microvascular Inflammation Are Associated With Inferior Kidney Graft Outcome, Regardless of Donor-Specific Antibodies - Novotny, Marek; Hruba, Petra; Kment, Martin; Voska, Ludek; Kabrtova, Katerina; Slavcev, Antonij; Viklicky, Ondrej (Frontiers in Medicine, 2021)
Background The prognostic role of intimal arteritis of kidney allografts in donor-specific antibody negative (DSA-) antibody-mediated rejection (ABMR) remains unclear. Methods 72 out of 881 patients who had undergone kidney transplantation in 2014-2017 exhibited intimal arteritis in biopsies performed during the first 12 months. In 26 DSA negative cases, the intimal arteritis was accompanied by tubulointerstitial inflammation as part of T cell-mediated rejection (TCMRV, N=26), intimal arteritis along with microvascular inflammation occurred in 29 DSA negative (ABMRV/DSA-) and in 19 DSA positive cases (ABMRV, DSA+, N=17). In 60 (83%) patients with intimal arteritis, the surveillance biopsies after antirejection therapy were performed. 102 patients with non-vascular ABMR with DSA (ABMR/DSA+, N=55) and without DSA (ABMR/DSA-, N=47) served as controls. Time to transplant glomerulopathy (TG) and to graft failure were the study endpoints. Results TG-free survival at 36 months was 100% in TCMRV, 85% in ABMR/DSA-, 65% in ABMRV/DSA-, 54% in ABMR/DSA+ and 31% in ABMRV/DSA+ (log rank p<0.001). Death-censored graft survival at 36 months was 98% in ABMR/DSA-, 96% in TCMRV, 86% in ABMRV/DSA-, 79% in ABMR/DSA+, and 64% in ABMRV/DSA+ group (log rank p=0.001). In surveillance biopsies, the resolution of rejection was found in 19 (90%) TCMRV, 14 (58%) ABMRV/DSA- and only 4 (27%) ABMRV/DSA+ patients (p=0.006). In the multivariable model, intimal arteritis as part of ABMR represented a significant risk for TG development (HR 2.1, 95% CI 1.2-3.8; p=0.012) regardless of DSA status but not for graft failure at 36 months. Conclusions Intimal arteritis as part of ABMR represented a risk for early development of transplant glomerulopathy regardless of the presence or absence of DSA. Intimal arteritis in DSA positive ABMR represented the high-risk phenotype.